2022
DOI: 10.1002/bse.3010
|View full text |Cite
|
Sign up to set email alerts
|

An interval‐valued composite indicator for energy efficiency and green entrepreneurship

Abstract: Promoting energy-efficient technologies can support green entrepreneurship via innovation creation. Energy efficiency policies and practices can promote cleaner productions and consumptions and environmental-friendly lifestyles in light of green growth goals. The foreseen strategy is twofold: it entails fostering energy-efficient technologies and supporting sustainable entrepreneurship. The work aims to measure energy efficiency by consistently constructing a new interval-based composite indicator using the Wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 101 publications
(105 reference statements)
0
10
0
Order By: Relevance
“…Therefore, BMs can assume a relevant role as enablers of sustainability (Porter & Kramer, 2011). Compared to the theory of traditional BMs and transaction costs that calls organizations to define the value proposition by considering companies, processes, customers, products, resources, and suppliers (Bagnoli et al, 2018; Bagnoli & Maura, 2021; Marinescu, 2012), SBMs additionally require an ecological or social value as mandatory pillars of the value proposition or the value creation process (Cosenz et al, 2020; Drago & Gatto, 2022; Nosratabadi et al, 2019; Secinaro, Brescia, et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, BMs can assume a relevant role as enablers of sustainability (Porter & Kramer, 2011). Compared to the theory of traditional BMs and transaction costs that calls organizations to define the value proposition by considering companies, processes, customers, products, resources, and suppliers (Bagnoli et al, 2018; Bagnoli & Maura, 2021; Marinescu, 2012), SBMs additionally require an ecological or social value as mandatory pillars of the value proposition or the value creation process (Cosenz et al, 2020; Drago & Gatto, 2022; Nosratabadi et al, 2019; Secinaro, Brescia, et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous research has concluded that successful business models will require that SMEs would relate the external drivers of eco-innovation (consumer preferences, incentives/penalties of the legal framework, stakeholders' pressure) to internal drivers, like increasing the market share while simultaneously reducing internal energy consumption and utilisation of raw materials (Calvo et al, 2022). Energy efficiency is a driver of entrepreneurship and one of the economic drivers for the development of a more effective business strategy (Drago & Gatto, 2022). Energy efficiency network programmes may be an external driver for increasing energy efficiency of SMEs, but assessing their effectiveness is still a significant issue (Johansson et al, 2022).…”
Section: Drivers Supporting the Implementation Of Energy Efficiency M...mentioning
confidence: 99%
“…Most of the existing studies focus on how to measure household livelihood resilience, for example, Marschke and Berkes proposed using local residents' satisfaction to measure resilience [34]; Fang Yiping et al proposed to use practical methods to measure livelihood quality, livelihood promotion, livelihood provision, and disaster stress [35]; Sina et al proposed a framework for livelihood resilience that includes four dimensions: individual livelihood coping ability, individual well-being, access to livelihood resources, and sociophysical robustness of the local community [36]. Meanwhile, a number of scholars have extended resilience to other research areas, such as Drago and Gatto, who suggested that energy policies are crucial to maintain the sustainability of renewable energy [37][38][39]; Aldieri et al pointed out that developing countries suffer from greater energy vulnerability and need to enhance national energy by improving renewable energy innovation to resilience [40].…”
Section: Literature Reviewmentioning
confidence: 99%